Chromobox 7/8 serve as independent indicators for glioblastoma via promoting proliferation and invasion of glioma cells - Zheng, Zong-Qing; Yuan, Gui-Qiang; Kang, Na-Ling; Nie, Qian-Qian; Zhang, Guo-Guo; Wang, Zhong (Frontiers in Neurology, 2022)
Background: Chromobox family, a critical component of the epigenetic regulators, participates in the tumorigenesis and progression of many malignancies. However, the roles of CBX family members (CBXs) in glioblastoma (GBM) remain largely unclear. Methods: We analyzed the mRNA expression of CBXs in tissues and cell lines by ONCOMINE and CCLE. The differential expression of CBXs at mRNA level in GBM was explored in The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databases with the "beeswarm" R package. The protein expression of CBXs in GBM was further examined on Human Protein Atlas (HPA). The correlations between CBXs and IDH mutation, and between CBXs and GBM subtypes were investigated in TCGA portal and CGGA database with the "survminer" R package. The alteration of CBXs and their prognostic value were further determined via cBioPortal and CGGA database with the "survival" R package. The univariate and multivariate analyses were performed to screen out the independent prognostic roles of CBXs in the CGGA database. Cytoscape was used to visualize the functions and related pathways of CBX family in GBM. Over-expression of CBX7 and under-expression of CBX8 through lentivirus transfection were utilized to explore their effects on the proliferation and invasion of glioma cells. Results: CBX family presented significantly differential expressions in pan-cancers. CBX2/3/5/8 were up-regulated, whereas CBX6/7 were down-regulated at mRNA level in GBM of TCGA and CGGA databases. Similarly, high expression of CBX2/3/5 and low expression of CBX6/8 were further confirmed at protein level in the HPA. CBX2/6/7 were positively correlated with IDH mutation, and CBX1/2/4/5/8 was closely related to GBM subtypes. CBX7 and CBX8 were screened out and presented the independent prognostic factors for GBM patient survival. GO and KEGG analyses indicated that CBXs were closely related to the histone H3-K36, PcG protein complex, ATPase, and Wnt pathway. Over-expression of CBX7 and under-expression of CBX8 significantly inhibited the proliferation and invasion of glioma cells in vivo and in vitro. Conclusion: Our results suggested that CBX7 and CBX8 served as independent prognostic indicators that promoted the proliferation and invasion of glioma cells, providing a promising strategy for diagnosing and treating GBM.